Root-Knot Nematode Resistance in Gossypium hirsutum Determined by a Constitutive Defense-Response Transcriptional Program Avoiding a Fitness Penalty - Ojeda-Rivera, Jonathan Odilón; Ulloa, Mauricio; Roberts, Philip A.; Kottapalli, Pratibha; Wang, Congli; Nájera-González, Héctor-Rogelio; Payton, Paxton; Lopez-Arredondo, Damar; Herrera-Estrella, Luis (Frontiers in Plant Science, 2022)
Cotton (Gossypium spp.) is the most important renewable source of natural textile fiber and one of the most cultivated crops around the world. Plant-parasitic nematode infestations, such as the southern Root-Knot Nematode (RKN) Meloidogyne incognita, represent a threat to cotton production worldwide. Host-plant resistance is a highly effective strategy to manage RKN; however, the underlying molecular mechanisms of RKN-resistance remain largely unknown. In this study, we harness the differences in RKN-resistance between a susceptible (Acala SJ-2, SJ2), a moderately resistant (Upland Wild Mexico Jack Jones, WMJJ), and a resistant (Acala NemX) cotton entries, to perform genome-wide comparative analysis of the root transcriptional response to M. incognita infection. RNA-seq data suggest that RKN-resistance is determined by a constitutive state of defense transcriptional behavior that prevails in the roots of the NemX cultivar. Gene ontology and protein homology analyses indicate that the root transcriptional landscape in response to RKN-infection is enriched for responses related to jasmonic and salicylic acid, two key phytohormones in plant defense responses. These responses are constitutively activated in NemX and correlate with elevated levels of these two hormones while avoiding a fitness penalty. We show that the expression of cotton genes coding for disease resistance and receptor proteins linked to RKN-resistance and perception in plants, is enhanced in the roots of RKN-resistant NemX. Members of the later gene families, located in the confidence interval of a previously identified QTL associated with RKN resistance, represent promising candidates that might facilitate introduction of RKN-resistance into valuable commercial varieties of cotton. Our study provides novel insights into the molecular mechanisms that underlie RKN resistance in cotton.